Datasets for sustainability reporting index of agricultural & plantation companies in Malaysia(Mendeley Data). - Nurfara Hasyikin Hanapi; Waleed M. Alahdal; Hafiza Aishah Hashim; Zalailah Salleh; Roshaiza Taha; Shayuti Mohamed Adnan (Data in Brief)
This article provides extensive information about how firms adhere to sustainability reporting guidelines set by Bursa Malaysia Sustainability Reporting Guideline (SRG) 2015 and Global Reporting Initiative (GRI) Sustainability Reporting Standard 2021. This research contains panel data for 56 Malaysian listed firms (agriculture and plantation sector) in Bursa Malaysia. This dataset was collected from 2016 to 2023. Information provided was obtained from the sustainability reports and annual reports of each firm, which had been downloaded from Bursa Malaysia website.The researcher can use the data effectively to create and calculate a sustainability reporting index that involves seventy-five sustainability reporting disclosure item and is comprised of three weighted sub-indices. The initial sub-index, “Economic Disclosure” consists of 8 items. The “Environmental Disclosure” sub-index consists of 31 items. The final sub-category, “Social Disclosure” consists of 36 items. Therefore, the researchers can assess companies using an overall index score provided by the unweighted sustainability reporting index.